Exploring the Lived Experience of Women Immediately Following Mastectomy: A Phenomenological Study. Issue 5 (September 2017) - Davies, Claire C.; Brockopp, Dorothy; Moe, Krista; Wheeler, Peggy; Abner, Jean; Lengerich, Alexander
Abstract : Background: In 2014, it is estimated that 232, 670 new cases of breast cancer occurred in the United States. Unilateral or bilateral mastectomy is a frequently chosen option for treating this disease. Objective: The purpose of this study was to explore, through an in-depth interview process, the lived experience of women immediately following mastectomy when they see their scars for the first time. Methods: Purposeful sampling was used until saturation was reached. In-depth interviews were conducted with 10 women related to their mastectomy experience. The data were analyzed using a phenomenological approach. Results: The following 8 themes emerged from the data; lasting impact, personal impact, relational impact, gratitude, support system, coping strategies, timing, and discomfort. Conclusions: The results of the study provide evidence that women face ongoing challenges following seeing their mastectomy scars for the first time that is not adequately addressed by healthcare professionals. Implications for Practice: Nurses and other healthcare professionals need to gain a better understanding of the difficulties perceived by women following seeing the scars from mastectomy and implement strategies to assist in successful adaptation to the experience.